"We pour, because of this he drinks": deviant behavior of the parish clergy in the 19th century (on the material of Kharkiv diocese). - Zaharchenko, Eugene (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences)
The article deals with the manifestations of deviant behavior of Orthodox parish clergy in the nineteenth century on the materials of Kharkiv diocese. It was determined that some models of clergy’s behavior stereotypes were differently interpreted by parish and diocesan authorities. Deviant behavior of parish clergy is interpreted as the intersection of bifurcation points of double morality in the society of the Russian Empire in the nineteenth century. It was established that alcohol consumption by priests in various communities could be interpreted both as a norm and a deviation at the same time.